Opsoclono-Myoclonic Syndrome Revealing a Neuroblastoma in an Infant: A Rare and Unusual Case Report - Mouhdi, S.; Aamri, H.; El-Fakiri, K.; Rada, N.; Draiss, G.; Bouskraoui, M. (British Journal of Healthcare and Medical Research, 2023)
Introduction Opsoclonomyoclonic syndrome (OMS) is an uncommon childhood illness. Opsoclonus, myoclonus, ataxia, and behavioral abnormalities are all symptoms. Long-term prognosis is dismal, however the introduction of novel immunotherapy regimens may improve it. Case report We present the case of an 18-month-old previously healthy newborn who was hospitalised for gait problem and widespread tremors that lasted four days, along with food vomiting and photophobia. A conscious patient with a 38°C temperature, a cerebellar syndrome, and aberrant palpebral and ocular myoclonic movements led us to suspect an opsoclonomyoclonic syndrome. The biological examination and brain CT were both normal, however the cerebral-medullary MRI revealed a signal anomaly. Given the close link between OMS and neuroblastoma, a thoraco-abdominal CT scan revealed a neuroblastoma. The child was transported to the paediatric oncology department, where he received surgical resection with chemotherapy, as well as corticosteroids, clonazepam, and antiepileptic medication. Oncologically and neurologically, the evolution was favorable. Conclusion : Although OMS is an uncommon condition in children, the fact that it has a significant connection with neuroblastoma allowed us to identify the diagnosis and begin therapy early, resulting in a positive patient outcome.